Micro-Doppler Ultrasonography-assisted Microsurgical Varicocelectomy: First Time in Turkiye - Ahmet Güdeloğlu; Gökhan Karakurt; Mesut Altan; Ali Ergen (Journal of Urological Surgery, 2020)

(untitled)
Objective:The magnification of the operative microscope or loop used in microsurgical varicocelectomy facilitates defining the anatomical structures. Even if the microsurgical approach is chosen, still, there is a 1% chance of iatrogenic testicular artery ligation and this may lead to the testicular atrophy. In this study, our aim was to present the efficacy and safety of the micro-Doppler ultrasound (USG) used during microsurgical varicocelectomy for the first time in Turkiye.Materials and Methods:A total of 46 patients with clinical varicocele underwent microsurgical varicocelectomy from May 2018 to July 2019. The da Vinci surgical system (CordaMed, İstanbul) was used in 5 patients and a standard operating microscope was used in 41 patients. Once the spermatic cord was brought up during the surgery, the velocity time integral microvascular Doppler system (Deltamed, Ankara) was used to identify the testicular vessels. The micro-Doppler USG probe allowed differentiation of the vessel by hearing the arterial pulsation audio.Results:Microsurgical varicocelectomy was performed in 46 patients and 48 spermatic cord units. The mean number of spermatic veins that were ligated in each spermatic cord unit was 3.05 (2-5) and each spermatic cord unit had mean 1.4 (1-3) spermatic arteries that were preserved. The mean follow-up duration was 9 months and none of the patients developed testicular atrophy after the procedure.Conclusion:The use of micro-Doppler USG in micro-surgical varicocelectomy seems to be an effective and safe method that facilitates the identification of testicular vessels. With the aid of micro-Doppler USG, even very small size arteries could be easily identified and iatrogenic damage could be avoided.